PERAN PENGAWAS SEKOLAH DALAM MEMBINA KOMPETENSI PEDAGOGIK GURU - Agus Faisal Asyha; Dedi Gunawan Saputra; Nining Huriati; Rasimin; MS Viktor Purhanudin; Rossa Ramadhona (EDU RESEARCH, 2024)
This study aims to analyze the role of school supervisors in fostering teachers' pedagogical competence, which includes the ability to design, implement and evaluate learning effectively. Pedagogical competence is one of the main competencies that teachers must have to improve the quality of education. The research method used is a qualitative approach with interview, observation and document analysis techniques. The results showed that school supervisors play a significant role in fostering teachers' pedagogical competence through academic supervision, mentoring and ongoing training. In addition, school supervisors also assist teachers in identifying student learning needs and designing innovative learning strategies. The constraints faced are lack of time and resources, but these can be overcome through good coordination between supervisors, principals and teachers. This study recommends strengthening the role of supervisors through intensive training and providing adequate facilities.